Rantai Nilai Global Manufaktur Tiongkok Pasca-COVID-19: Analisis Input-Output dan Implikasi Strategis bagi Indonesia - Fadhillah Akbar Salam; Reza Triarda (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2026)
The global supply chain is a crucial aspect of the dynamics of the global value chain within the manufacturing sector. China is known as the